2010
DOI: 10.1016/j.homp.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for studying homeopathy and high dilutions: Conceptual critical review

Abstract: Systematic analysis of the selected papers yielded evidence of some important intrinsic features of high dilution studies performed in animal models: a) methodological quality was generally adequate, some aspects could be improved; b) convergence between results and materia medica is seen in some studies, pointing toward to the possibility of systematic study of the Similia principle c) both isopathic and Similia models seem useful to understand some complex biological phenomena, such as parasite-host interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 71 publications
1
29
0
1
Order By: Relevance
“…Nevertheless, in the recent scientific literature about homeopathy, there are many studies searching to demonstrate the efficacy of its effect, but few works are devoted to the comprehension of physiopathological changes in tissues after the exposition of animals to these medicines [6, 27, 28]. Is from this point of view that the present work was built; through a detailed study of the inflamed connective tissue, considering the subsets of cells that migrate to it, the vessels behavior, and time-dependent dynamic of this process under the action of Arnica montana 6cH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in the recent scientific literature about homeopathy, there are many studies searching to demonstrate the efficacy of its effect, but few works are devoted to the comprehension of physiopathological changes in tissues after the exposition of animals to these medicines [6, 27, 28]. Is from this point of view that the present work was built; through a detailed study of the inflamed connective tissue, considering the subsets of cells that migrate to it, the vessels behavior, and time-dependent dynamic of this process under the action of Arnica montana 6cH.…”
Section: Discussionmentioning
confidence: 99%
“…This particular feature is one of the most difficult challenges of the scientific research in this field because of the technical difficulty of its experimental demonstration. Indeed, few experimental studies about are found in the literature [16]. Thus, the experimental demonstration of this particularity and the comprehension of its mechanisms can be useful tools to solve the chronic controversies about homeopathy efficacy, often seen in clinical trials [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…preparations of their enantiomers (enantiomer: either of a pair of optical isomers that are mirror images of each other). These experiments constituted the first time such stereochemical considerations had been tested in homeopathic research [1]. This was confirmed by examination at the Australian, US, and European patent offices in relation to PCT/AU2003/000219 [2].…”
Section: Introductionmentioning
confidence: 86%
“…The pure water (vehicle) was chosen as negative control because, as observed in a systematic review [2], contrary to what is observed in vitro , the succussion of water seems to be irrelevant in studies about high dilutions performed in vivo .…”
Section: Methodsmentioning
confidence: 99%